Pemaksaan Pernikahan Korban Pemerkosaan Dengan Pelaku Ditinjau Dari Hukum Positif Indonesia - Rizka, Rizka; Prasetyo, Achmad Dzaki (Fakultas Hukum, Universitas Boyolali, 2024)
Rape is a despicable act that violates the dignity of a woman. Not only women, even children are often victims of these barbaric acts. And not a few of these legal problems are considered over by marrying the victim to the perpetrator. This research has a goal that focuses on examining and analyzing the legal arrangements that apply in Indonesia to the forced marriage of victims and legal protection efforts and the impact that occurs to victims if married to the perpetrator of rape. The research method used is normative juridical by processing primary, secondary, and tertiary data which are all related to the topic raised. The results of the discussion of this research are based on article 10 paragraph (1) and (2) of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, forcing the victim's marriage to the perpetrator is coercion of rape and is punishable by 9 (nine) years imprisonment and / or a fine of Rp. 200,000,000 (two hundred million rupiah).